Biphasic Ferrogels for Triggered Drug and Cell Delivery. Issue 11 (26th May 2014) - Cezar, Christine A.; Kennedy, Stephen M.; Mehta, Manav; Weaver, James C.; Gu, Luo; Vandenburgh, Herman; Mooney, David J.
<x xml:space="preserve">Abstract</x> Ferrogels are an attractive material for many biomedical applications due to their ability to deliver a wide variety of therapeutic drugs on‐demand. However, typical ferrogels have yet to be optimized for use in cell‐based therapies, as they possess limited ability to harbor and release viable cells. Previously, an active porous scaffold that exhibits large deformations and enhanced biological agent release under moderate magnetic fields has been demonstrated. Unfortunately, at small device sizes optimal for implantation (e.g., 2 mm thickness), these monophasic ferrogels no longer achieve significant deformation due to a reduced body force. A new biphasic ferrogel, containing an iron oxide gradient, capable of large deformations and triggered release even at small gel dimensions, is presented in this study. Biphasic ferrogels demonstrate increased porosity, enhanced mechanical properties, and potentially increased biocompatibility due to their reduced iron oxide content. With their ability to deliver drugs and cells on‐demand, it is expected that these ferrogels will have wide utility in the fields of tissue engineering and regenerative medicine.